# How do you solve # x/3 - x/6 = 2#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation x/3 - x/6 = 2, you can follow these steps:

- Find a common denominator for the fractions, which in this case is 6.
- Multiply both sides of the equation by 6 to eliminate the denominators.
- Simplify the equation by distributing and combining like terms.
- Solve for x by isolating it on one side of the equation.
- Check your solution by substituting it back into the original equation.

The solution to the equation x/3 - x/6 = 2 is x = 12.

By signing up, you agree to our Terms of Service and Privacy Policy

- How do you add #3/(x-7)+5/(x+2)#?
- How do you simplify #(3x)/(6x^2) times (2y-6)/(y-3)#?
- How do you simplify #(7 / t) + (2 / t)#?
- If y varies inversely as the cube of x and x=2.5 when y=0.015, how do you find y when x=5?
- How do you solve the equation and identify any extraneous solutions for #x/(x-2) - 5 = 2/(x-2)#?

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7